Transcranial Magnetic Resonance Imaging-Guided Focused Ultrasound Treatment at 1.5 T: A Retrospective Study on Treatment- and Patient-Related Parameters Obtained From 52 Procedures - Gagliardo, Cesare; Marrale, Maurizio; D'Angelo, Costanza; Cannella, Roberto; Collura, Giorgio; Iacopino, Gerardo; D'Amelio, Marco; Napoli, Alessandro; Bartolotta, Tommaso Vincenzo; Catalano, Carlo; Lagalla, Roberto; Midiri, Massimo (Frontiers in Physics, 2020)
To present a retrospective analysis of patient- and sonication-related parameters of a group of patients treated with a transcranial magnetic resonance imaging-guided focused ultrasound (tcMRgFUS) system integrated with a 1.5-T MRI unit. The data obtained from 59 patients were retrospectively reviewed for this study. The following data were mainly collected: skull density ratio (SDR), skull area (SA), transducer elements (Tx), and estimated focal power at target (FP). For each treatment stage, we calculated the number of sonication (Sn), sonication power (Sp), measured power (Smp), sonication duration (Sd), energy (E), measured energy (Em), maximum temperature (Tmax), and MR thermometry plane orientation. Furthermore, the time delay between each sonication (St) and the total treatment time (Tt) were recorded. Fifty-two patients (40 males and 12 females; age – 64.51 ± SD 11.90; range 26–86), who underwent unilateral Vim thalamotomy (left = 50, 96.15%; right = 2, 3.85%) for medication refractory essential tremor (n=39; 78%) or Parkinson tremor (n=13; 22%) were considered. A total of 1068 (95.10%) sonication were included in our final analysis (average Sn per treatment: 20.65 ± 6.18; range 13–41). The energy released onto the planned target was found to decrease with the SDR for all temperature ranges. A positive correlation was observed between the slope of Tmax vs. Em plot and the SDR (R2=0.765; p<0.001). In addition, the Tmax was positively correlated with SDR (R2=0.398; p<0.005). On the contrary, no significant correlation was found between SDR and SA or Tx. An analysis of the MR Thermometry scanning plane indicated that, at our site, the axial and the coronal planes were mostly used. Our results confirm the factors that significantly influence the course of a tcMRgFUS procedure even when a 1.5-T MRI scanner is used for procedure guidance. The experience we gained in this study indicates that the SDR still remains one of the most significant technical parameters to be considered in a tcMRgFUS procedure. The possibility of prospectively setting the sonication energy according to the presented curves of energy delivery as a function of SDR for each treatment stage could provide a further understanding and awareness of this technology.